Some Welfare Aspects of International Migration - Berry, R. Albert; Soligo, Ronald (Journal of Political Economy, 1969)
The welfare implications of factor flows between countries, unlike those of flows of goods, have received very little theoretical treatment to date. It is widely accepted that emigration of highly skilled people constitutes a loss to a country (Oteiza 1965, Perkins 1966) and fairly generally agreed that emigration of unskilled labor can improve the lot of the remaining populace. Yet these propositions are not self-evident.Grubel and Scott (1966b) have challenged these views, concluding that, in general, if each person is paid his marginal product, no loss accrues to the remaining population from emigration. Although arguing in the context of a "brain drain," they have analyzed only the effects of a marginal outflow of human capital. When the effects of nonmarginal migration (which the word "drain” suggests) are considered, their conclusions do not hold. (Neither, however, do those generally accepted propositions referred to in the previous paragraph.) Yet the concern over the "brain drain" reflects the fact that nonmarginal flows have been and still are by no means rare. This is true even for unskilled labor. The analysis here is carried out under the limiting assumption of classical markets (for both goods and factors) within a country, but (at least for factors) not between countries. A gain (loss) is said to occur whenever the total income accruing to nonmigrants increases (decreases). This welfare criterion implicitly assumes that the marginal utility of income is the same for all of the persons in the nonmigrating groups. It is assumed, first, that the emigration is a once and for all affair and that the supply of resources to the domestic economy is perfectly inelastic. Because of the latter assumption, this case may be thought of as referring to the very short run in which resource supplies do not adjust to the impact of the migration. Given the assumptions used, to be spelled out below, loss occurs in all cases except where the emigrants own a relatively high proportion of the capital in the economy and do not take it with them. External effects related to the emigrants, increasing returns to scale, and other conditions, can affect the results, but since the direction of such effects is usually clear, the only interesting question is whether they are quantitatively important. The other cases discussed allow for the readjustment of factor supplies and factor proportions to the migration. If there are only two factors, capital and labor, the results depend on the relative propensity to hold wealth of emigrants and nonemigrants and on whether the emigrants take their capital with them or not. Loss occurs in all cases except where the emigrants have relatively high propensities to hold wealth but leave a large part of their capital behind, or (a special case) where they own the same amount of capital per person as the nonemigrants and take it all with them. If three factors are introduced, by distinguishing between skilled and unskilled labor, the result depends jointly on the relative propensities to hold wealth, the skill levels of migrants and nonmigrants, the ease of transforming unskilled into skilled labor, and the extent to which emigrants take their (nonhuman) capital with them. In general, the conclusion is that emigration leads to loss.